Influence of manufacturing shrinkage and microstructural features on the strength properties of carbon fibers/PEEK composite material - E.V. Lomakin; B.N. Fedulov; A.N. Fedorenko (Fracture and Structural Integrity)
This research discusses the micromechanical modelling for thermoplastic composite material. Elastoplastic and damage model for PEEK matrix composite with the dependency of properties to stress state is presented. Plasticity initiation conditions and failure criterion are analyzed. The influence of manufacturing residual stresses is considered. All typical engineering experiments for neat PEEK under different stress state are good predicted by the model. Numerical experiment for macro-properties estimation based on micromechanical model is conducted and the results are compared with the test data